2003
DOI: 10.1007/s00701-003-0119-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intravascular perfusion of cooled crystalloid solution on cold-induced brain injury using an extracorporeal cooling-filtration system

Abstract: Occlusion of three main arteries induced ischaemia under critical threshold in canine brains. Under this condition, intravascular cooling with crystalloid solution suppressed accumulation of extracellular glutamate and reduced tissue damage in the early phase after cold-induced brain injury, as cerebroprotective effects. This information suggests that a method employing brain hypothermia via intra-arterial cooling with an extracorporeal cooling-filtration system has potential to achieve successful, safe, selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Noguchi et al 12 concluded that producing SBC by perfusion of saline into the subdural space was effective and might be used in neurosurgery. Furuse et al 13 showed that perfusion of the carotid artery was another way of producing SBC. Rapid induction of cooling by intravenous administration of cold crystalloid is another technique.…”
mentioning
confidence: 99%
“…Noguchi et al 12 concluded that producing SBC by perfusion of saline into the subdural space was effective and might be used in neurosurgery. Furuse et al 13 showed that perfusion of the carotid artery was another way of producing SBC. Rapid induction of cooling by intravenous administration of cold crystalloid is another technique.…”
mentioning
confidence: 99%
“…This technique cooled the brain but did not significantly interfere with body temperature [65]. Furuse et al evaluated cerebral metabolic change during brain hypothermia with intravascular perfusion of cooled crystalloid solution using an extracorporeal cooling-filtration system and cerebroprotective effects of this hypothermia on brain injury in an animal model [66]. The result suggested that brain hypothermia via intra-arterial cooling with an extracorporeal cooling-filtration system had potential to achieve successful, safe, selective brain cooling.…”
Section: Cooling Through Perfusing Cold Bloodmentioning
confidence: 95%
“…KEY WORDS: cardiopulmonary resuscitation; hypothermia; extracorporeal cooling hr), similar to the very efficient cardiopulmonary bypass and the technique used by Furuse et al (28). Behringer et al (32) used extracorporeal blood cooling.…”
Section: Conclusion: Rapid Induction Of Mild Hypothermia Is Feasiblementioning
confidence: 96%
“…Application of cold saline directly into the circulatory system was demonstrated to be effective both for reducing core temperature (27) and brain only (28). The rates of cooling using these methods were substantially faster compared with external cooling.…”
mentioning
confidence: 98%
See 1 more Smart Citation